Automated Notes Maker from Audio Recordings - Manoj Kumar A; Janani P; Siva Subramanian G; Kumaragurubaran K; Sundari P (Journal of Image Processing and Intelligent Remote Sensing, 2023)
Automated note-taking software uses machine learning and natural language processing to transcribe spoken words from audio recordings. In the current fast-paced environment, individuals and organisations regularly have to manage enormous amounts of data in the form of audio recordings, video recordings, and text documents. The manual summarization and transcription of such data can be laborious and time-consuming. This problem has been resolved by automated note-taking software for audio recordings. Natural language processing (NLP) and machine learning techniques are used by these technologies to transform spoken words into text, which is subsequently used to build a summary or set of notes. This project report looks at the effectiveness and utilisation of automated note-taking software for audio recordings.To transform the audio recordings of online classes into text-based PDF or Word documents, which are voice-based in correctness, a module for automated notes creator from audio recordings is shown in this presentation.